Return migration in later life : international perspectives - Percival, John (Bristol : Policy Press, 2013)
The main objective of this edited volume is to explore the motivations, decision making processes, and consequences, when older people consider or accomplish return migration to their place of origin; and also to raise the public policy profile of this increasingly important subject.
Title from publisher's bibliographic system (viewed on 03 Feb 2022).
Keywords: Return migration; Older people; Return migrants